STRATEGI INKUBASI BISNIS STARTUP MAHASISWA IPB MELALUI PEMBIAYAAN SYARIAH BPRS BOTANI DENGAN PENDEKATAN ANP-SWOT - Raul Ranatama (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2022)
The high level of education in Indonesia can be seen by IPB and BPRS Botani by creating a business incubation program for students. The purpose of this research is to analyze internal and external factors and identify strategic priorities for the IPB students' business development through BPRS Botani sharia financing. This study uses the ANP–SWOT method. The results show that strength is the main priority in incubating the IPB students' startup business through BPRS Botani sharia financing. Strengths, weaknesses, opportunities, and threats variables are most influenced by IPB's experience and ability (professionalism) in managing business incubators. Many BPRS human resources are inexperienced in providing student business financing, creative economy programs that can support startup development programs, and the difficulty dividing time between main tasks and business inventory when involving lecturers or other campus human resources. The most preferred strategy to be applied is professionalism and experience to increase trust and common perception in realizing the ideal business.